Evaluasi Dan Perbaikan Rancangan Antarmuka Pengguna Aplikasi MboisApp Menggunakan Metode Goal-Directed Design - Revina Laksmi Permata Hati; Retno Indah Rokhmawati; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
MboisApp is an Android-based mobile application that aims to provide tourism information and make it easier for users to plan tourist destinations in Malang. Usability evaluation aims to identify problems faced by users when interacting with applications and find opportunities to improve the user experience. Usability evaluation was directed to 10 respondents by dividing 2 groups of of tourists based on geographical aspects, by measuring 3 metrics of usability as effectiveness using completion rate, efficiency using overall relative efficiency, and satisfaction using System Usability Scale (SUS) questionnaire. The results of the initial evaluation show 13 usability problems that need to be fixed in order to make it easier for users to achieve their goals in using the application, so in this study using the Goal Directed Design (GDD) method. After improving the interface using the GDD method, a final usability evaluation is carried out on the MboisApp application improvement design. The results of the final evaluation of the usability get an increase in the value of each metric. The initial effectiveness value was 64.2% to 94.2%, the initial efficiency value was 57.4% to 91.3% and the satisfaction score of all was 40.25 to 80.5. The results of improving the interface design in the MboisApp application using the GDD method prove that it can increase the usability value of the previous MboisApp application design. Keywords: usability, usability evaluation, goal-directed design